HUBUNGAN ANTARA TINGKAT OBESITAS DENGAN KONSEP DIRI PADA REMAJA PUTRI DI KEDUNGGUPIT SIDOHARJO WONOGIRI - Sri Yulianti, Tunjung; -, Dinar Ariasti (Politeknik Insan Husada Surakarta, 2015)
Introduction: This study is the estimate of WHO as many as 315 million people worldwide are categorized as obese with more women than men. Among adolescent obesity is a worrying problem, obtained the condition of the majority of young women who are overweight (obese) with confidence is lackingPurpose of the study: is to determine the number of young women who are obese, and the concept of self-possessed young women who are overweight or obese can be called, as well as to determine the relationship between self-concept levels of obesity in adolescent girls. Subjects: of this study were all obese young women between 14-22 years of age.Methode : This research method using cross sectional approach The study was conducted by measuring the weight and giving questioner to the teenagers who had weight included in obesity. This data was analyzed using chi square.Results: showed the average self-concept is owned by teenagers who are obese is a negative self-concept, with the data processing SPSS value of p = 0.014, which means the value of p <0.05 so ha ho accepted and rejected, then there is a relationship between the degree of obesity with the concept of self in adolescent girls.Conclusion : there is a relationship between the level of obesity in the young women's self-concept Kedunggupit Sidoharjo Wonogiri.Keywords: obesity rates, self-concept